Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Step-by-step explanation:
Hello there!
Here is the solution to our problem:
To begin with, we give our equations labels as below;
3m − n = 2 ...................eq.1
2m + n = − 7 ..................eq.2
Then, Let's manipulate eq.2
2m + n = − 7
n = -7 - 2m ...............eq3
And finally substitute the manipulated eq.3 into eq.1
3m − n = 2
3m − (-7 - 2m) = 2
3m + 7 + 2m = 2
5m = -5
m = -1
Substitute the value of m into eq.3
n = -7 - 2(-1)
= -5
In terms of x and y;
(x,y) : (m, n) => (-1, -5)
Therefore (m, n) = (-1, -5)
I hope this helps.
Have a nice studies.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.